2017
DOI: 10.1002/aur.1879
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effects of age, pubertal development, and symptom profile on cortisol rhythm in children and adolescents with autism spectrum disorder

Abstract: Previous studies in children with autism spectrum disorder (ASD) have shown elevated evening cortisol; however, few studies have examined diurnal rhythm in adolescents with ASD. Adolescence is a time of significant physical and psychological change, and dysregulation of the hypothalamic-pituitary-adrenal axis may put adolescents with ASD at increased risk for internalizing disorders, such as anxiety and depression. The extent to which cortisol levels are associated with age, puberty and symptom profile was exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 67 publications
7
41
1
Order By: Relevance
“…In a large study of 113 adolescents (7–17 years) with ASD, hypersecretion of cortisol was observed in the evening, but not at any other time point in comparison to age‐ and sex‐matched controls. However, the diurnal slope of the ASD group was also blunted [Muscatello & Corbett, ]. Both age and puberty were significant predictors of evening cortisol levels, with increased age and pubertal status being associated with higher cortisol levels [Muscatello & Corbett, ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a large study of 113 adolescents (7–17 years) with ASD, hypersecretion of cortisol was observed in the evening, but not at any other time point in comparison to age‐ and sex‐matched controls. However, the diurnal slope of the ASD group was also blunted [Muscatello & Corbett, ]. Both age and puberty were significant predictors of evening cortisol levels, with increased age and pubertal status being associated with higher cortisol levels [Muscatello & Corbett, ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the diurnal slope of the ASD group was also blunted [Muscatello & Corbett, ]. Both age and puberty were significant predictors of evening cortisol levels, with increased age and pubertal status being associated with higher cortisol levels [Muscatello & Corbett, ]. Corbett et al [] and Richdale and Prior [] also demonstrated hypersecretion in children with ASD aged 6–12 and 4–14 years, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research has emerged over the last few decades examining the activation of the HPA axis in children and adolescents with ASD (Muscatello & Corbett, 2018; Taylor & Corbett, 2014). Although the majority of the studies have been conducted on the reactivity of the HPA axis in children (Corbett, Schupp, & Lanni, 2012; Lanni, Schupp, Simon, & Corbett, 2012; Nir et al, 1995; Schupp, Simon, & Corbett, 2013; Tani et al, 2005; Tordjman et al, 2009) studies with adolescents are emerging (Edmiston, Blain, & Corbett, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Parents completed the five-item measure, indicating on a four-point scale ranging from: not yet begun to complete. The PDS was originally developed as a self-report measure of pubertal development; however, it also has been used as a parent-report pubertal development measure (Muscatello & Corbett, 2018 ). While parents were the ones completing the measure, we encouraged all parents to consult with their child to confirm their answers.…”
Section: Methodsmentioning
confidence: 99%